Paraboloid Vertex and Axis (Simplified)

Geometry Level 3

A paraboloid is given by z = x 2 + y 2 5 z = x^2 + y^2 - 5 . The points lying on its surface are subjected to the linear transformation

p = A p \mathbf{p'} = A \mathbf{p}

where p = ( x , y , z ) \mathbf{p} = (x, y, z) is a point on the paraboloid surface, and p = ( x , y , z ) \mathbf{p'} = (x', y', z') is its image under the above linear transformation. The matrix A A is given by

A = [ 1 4 6 4 2 5 6 5 3 ] A = \displaystyle \begin{bmatrix} 1 && 4 && 6 \\ 4 && 2 && -5 \\ 6 && -5 && 3 \end{bmatrix}

Under this transformation, the surface of the original paraboloid is reshaped into another paraboloid. Find the vertex r 0 \mathbf{r_0} of the new paraboloid, and the unit vector u \mathbf{u} along its axis of symmetry that is pointing in the direction that the paraboloid opens up. Let r 0 = ( r 0 x , r 0 y , r 0 z ) \mathbf{r_0} = (r_{0x}, r_{0y}, r_{0z} ) and u = ( u x , u y , u z ) \mathbf{u} = ( u_x, u_y, u_z ) , find r 0 x + r 0 y r 0 z + 100 ( u x + u y + u z ) - r_{0x} +r_{0y} -r_{0z} + 100( u_x + u_y+ u_z) .


The answer is 117.9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Yuriy Kazakov
Apr 30, 2021

Fine problem. I use Python. I find point ( x M , y M , z M ) (x_M , y_M, z_M) on surface

1865 x 2 774 x y + 1220 x z + 5306 x 2853 y 2 4368 y z 10991 y 2125 z 2 + 12128 z + 718205 = 0 -1865 x^2 - 774 xy + 1220 xz + 5306x - 2853y^2 - 4368 y z - 10991y - 2125z^2 + 12128z + 718205=0

with

K ( x M , y M , z M ) = M a x ( K ( x , y , z ) ) K(x_M,y_M,z_M)=Max( K(x,y,z)) .

K ( x , y , z ) K(x,y,z) is here GaussianCurvature - formula ( 16 ) (16) .

x M = 15.204 x_M=-15.204

y M = 24.896 y_M= 24.896

z M = 29.994 z_M= -29.994

K = 0.13645128106808901 K=0.13645128106808901

A n s w e r = 117.8718640777565 Answer= 117.8718640777565

Hosam Hajjir
Apr 29, 2021

The original paraboloid can be written in matrix-vector form as

p T Q p + a T p + b = 0 ( 1 ) p^T Q p + a^T p + b = 0 \hspace{24pt} (1)

where

Q = [ 1 0 0 0 1 0 0 0 0 ] Q = \begin{bmatrix} 1 && 0 && 0 \\ 0 && 1 && 0 \\ 0 && 0 && 0 \end{bmatrix}

a T = [ 0 , 0 , 1 ] a^T = \begin{bmatrix} 0, 0, -1 \end{bmatrix}

b = 5 b = -5

Now, since the coordinate vector of a point on the new paraboloid is p = A p p' = A p , then p = A 1 p p = A^{-1} p' . Plugging this into the above equation results in

p T A T Q A 1 p + a T A 1 p + b = 0 ( 2 ) p'^T A^{-T} Q A^{-1} p' + a^T A^{-1} p' + b = 0 \hspace{24pt} (2)

This is the equation of the new paraboloid. To identify the vertex and axis, we have to put it in the standard form of a general paraboloid which is,

( p r 0 ) T R D R T ( p r 0 ) + a T R T ( p r 0 ) = 0 ( 3 ) (p - r_0)^T R D R^T (p - r_0) + a^T R^T (p - r_0) = 0 \hspace{24pt} (3)

where D D is a diagonal matrix with D 11 > 0 , D 22 > 0 , D 33 = 0 D_{11} > 0 , D_{22} > 0 , D_{33} = 0 , R R is a rotation matrix, r 0 r_0 is the vertex, and a a is as above. The third column of matrix R R is along the axis of the paraboloid.

The standard equation of a general paraboloid can be multiplied through by a nonzero constant, and this results in

λ ( p r 0 ) T R D R T ( p r 0 ) + λ a T R T ( p r 0 ) = 0 ( 4 ) \lambda (p - r_0)^T R D R^T (p - r_0) + \lambda a^T R^T (p - r_0) = 0 \hspace{24pt} (4)

We want to find the value of λ , D , R , r 0 \lambda, D, R, r_0 such that equations ( 2 ) , ( 4 ) (2) , (4) are identical, that is,

A T Q A 1 = λ R D R T ( 5 ) A^{-T} Q A^{-1} = \lambda R D R^T \hspace{24pt} (5)

A T a = 2 λ R D R T r 0 + λ R a ( 6 ) A^{-T} a = - 2 \lambda R D R^T r_0 + \lambda R a \hspace{24pt} (6)

and

b = λ r 0 T R D R T r 0 λ a T R T r 0 ( 7 ) b = \lambda r_0^T R D R^T r_0 - \lambda a^T R^T r_0 \hspace{24pt} (7)

By diagonalizing A T Q A 1 A^{-T} Q A^{-1} we immediately find R R and the diagonal matrix λ D \lambda D . Next, by pre-multiplying equation ( 6 ) (6)

by R T R^T it becomes

R T A T a = 2 λ D R T r 0 + λ a ( 8 ) R^T A^{-T} a = - 2 \lambda D R^T r_0 + \lambda a \hspace{24pt} (8)

The third row of this vector equation reads,

( R T A T ) 3 = λ - (R^T A^{-T})_3 = - \lambda

because the third row of matrix D D is a row of zeroes. Thus, we have found λ \lambda , and therefore, matrix D D is now known.

Finally, we have to find the vertex r 0 r_0 . Plugging the values we have for R , D , λ R , D , \lambda into equation ( 6 ) (6) , we can solve this system of equations for r 0 r_0 . The solution is of the form r 0 = v 0 + t v 1 r_0 = v_0 + t v_1 where t t is yet to be determined. To determine it, we use equation ( 7 ) (7) . The term r 0 T R D R T r 0 r_0^T R D R^T r_0 in equation ( 7 ) (7) , can be simplified by using equation ( 6 ) (6) , where we note that pre-multiplying by r 0 T r_0^T , and re-arranging, results in,

λ r 0 T R D R T r 0 = 1 2 ( λ r 0 T R a r 0 T A T a ) \lambda r_0^T R D R^T r_0 = \dfrac{1}{2} \left( \lambda r_0^T R a - r_0^T A^{-T} a \right)

Plugging this into equation ( 7 ) (7) results in

2 b = ( λ a T R T a T A 1 ) r 0 ( 9 ) 2 b = (- \lambda a^T R^T - a^T A^{-1} ) r_0 \hspace{24pt} (9)

Equation ( 9 ) (9) , coupled with r 0 = v 0 + t v 1 r_0 = v_0 + t v_1 can be used directly to find the constant t t . Hence r 0 r_0 is now determined.

That was an outline of the solution method for this problem. For the numerical results, a small computer program can be used, provided you have a routine for finding the eigen structure of a symmetric matrix.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...